Investigating waste management strategies in the extended producer responsibility in Iran - Hassan Passandideh Tashakori; Parvin Farshchi; Dariush Karimi; Seyed Masoud Monavari (علوم محیطی)
Introduction: In many developed countries, Extended Producer Responsibility (EPR), which is among the successful waste management programs, has been adopted and implemented as a policy approach. EPR is aimed at reducing the financial load that waste collection and management imposes on local governments, especially waste that requires complicated and costly treatment and recovery processes. It is an efficient tool in resource management according to which the responsibility for goods and products rests with their producers until the end of their life cycle. In Iran, in accordance with Article 4 of the Waste Management Act and Article 12 of its Executive Bylaw, the National Environmental Fund is responsible for collecting taxes levied on producers and importers of goods and products that produce waste and for offering facilities to units engaged in resource recovery. Yes, it has not been implemented for various reasons. The present paper seeks to implement the responsibility of producers to manage waste from the consumption of goods in Iran.   Material and methods: In this research, using a questionnaire, the opinions of 60 experts and domestic experts in the field of research were used. First, the data and information received from the individual survey forms were validated, and then the best strategies were analyzed according to the SWOT model. To determine the attractiveness, the data entered the QSPM quantitative planning matrix and the priorities were determined accordingly. By examining the legal challenges of implementing waste management regulations and identifying the obstacles of the implementation of expanding the responsibility of the producer in the country, and the results of this research, appropriate strategies for its implementation were also presented.  Results and discussion:  The most important problems causing the failure to implement EPR in Iran were (1) the lack of an effective and efficient legal mechanism to require cooperation and coordination between the governmental agencies for collecting the taxes levied on producers and importers of goods and products, the consumption of which leads to the production of waste that is dangerous for the environment, (2) the failure in the timely establishment of the National Environmental Fund, (3) the all-encompassing list of goods and products subject to EPR, (4) a large number of goods and products subject to EPR and (5) the identical tax levied on the various goods and products subject to EPR. However, if EPR is implemented in Iran and the National Environmental Fund offers facilities for setting up industrial waste management centers, especially in resource recovery, and investment by the private sector in the industries and technologies related to waste recovery is supported, the environment will be protected and waste will be managed systematically. In addition, business activities will flourish and sustainable jobs and income will be created. Moreover, economic growth will result from resource recovery and conversion of waste into energy and new products. This will play a substantial role in self-sufficiency, resulting in independence from foreign countries for the provision of raw materials and prevention of foreign currency outflows to procure them. Therefore, it is necessary to take the required measures to resolve the problems and difficulties in the way of EPR in Iran and also to launch a comprehensive and integrated information system for producers of goods and products subject to waste management. Moreover, the list of such goods and products should be more limited and more transparent, and the Department of Environment and other related organizations should also supervise the way of levied taxes collection and how the facilities are granted by the National Environmental Fund. They should also supervise the environmental performance of those engaged in resource recovery.  Conclusion: When designing products, manufacturers of goods and consumables accept their legal and economic responsibility in order to minimize the environmental effects and take action to reduce the destructive effects of products and waste management of materials and goods in the environment